KREATIVITAS SISWA PADA TEKNOLOGI MASA KINI - Wenny Liana Simaremare; Melvana Evriani Hutagalung; Elis Kasih Marpaung; Damayanti Nababan (CV. Denasya Smart Publisher, 2024)
Student creativity in using today's technology is an important focus in the context of modern education. This background highlights the challenges faced in developing student creativity, including a lack of recognition of the importance of creativity, an overly structured learning environment, and a lack of support from the surrounding environment. The purpose of this research is to explore the concept of student creativity, analyze the challenges in developing student creativity, and offer effective strategies for developing student creativity. The research method used is literature study to collect data about the concept of student creativity and the challenges in developing it, as well as preparing recommendations based on thematic analysis. The results show that developing student creativity requires a supportive learning environment, stimulating learning strategies, and strong partnerships between educators, parents, and the community. Practical implications of this research include improving teacher training, integrating technology in the curriculum, increasing access to resources, promoting collaboration and exchange of ideas, and creativity-oriented evaluation and assessment. By heeding these recommendations, we can help ensure that every student has the opportunity to develop their full creative potential and become the influential innovators of tomorrow.